The role of customer management capabilities in public–private partnerships. (19th September 2017) - Canhoto, Ana Isabel; Meadows, Maureen; Ball, Kirstie; Daniel, Elizabeth; Dibb, Sally; Spiller, Keith
Abstract : Commercial organisations are increasingly asked to perform tasks traditionally associated with governmental bodies, such as law enforcement. The rationale for these public–private partnerships is that there are synergies between traditional business skills and those required to achieve certain societal goals. However, there is a lack of research into whether this is, indeed, the case. This paper addresses this gap by investigating one particular type of public–private partnership: anti-money laundering (AML). The study explores the potential synergies between customer relationship management (CRM) and those required for AML. A quantitative survey-based approach is used to identify the overlaps and connections between these two areas of competence. The findings reveal tensions between financial institutions' dual roles as both commercial organisations and players in the battle against money laundering. The consequences for these firms are explored, and the wider implications for other organisations supplying non-commercial services to government are considered.